T-kininogen inhibits kinin-mediated activation of ERK in endothelial cells - ELIAS LEIVA-SALCEDO; VIVIANA PEREZ; CLAUDIO ACUÑA-CASTILLO; ROBIN WALTER; FELIPE SIERRA (Biological Research, 2002)
Serum levels of T-kininogen increase dramatically as rats approach the end of their lifespan. Stable expression of the protein in Balb/c 3T3 fibroblasts leads to a dramatic inhibition of cell proliferation, as well as inhibition of the ERK signaling pathway. T-kininogen is a potent inhibitor of cysteine proteinases, and we have described that the inhibition of ERK activity occurs, at least in part, via stabilization of the MAP kinase phosphatase, MKP-1. Since fibroblasts are not a physiological target of T-kininogen, we have now purified the protein from rat serum, and used it to assess the effect of T-kininogen on endothelial cells. Adding purified T-kininogen to EAhy 926 hybridoma cells resulted in inhibition of basal ERK activity levels, as estimated using appropriate anti-phospho ERK antibodies. Furthermore, exogenously added T-kininogen inhibited the activation of the ERK pathway induced by either bradykinin or T-kinin. We conclude that the age-related increase in hepatic T-kininogen gene expression and serum levels of the protein could have dramatic consequences on endothelial cell physiology, both under steady state conditions, and after activation by cell-specific stimuli. Our results are consistent with T-kininogen being an important modulator of the senescent phenotype in vivo